2022
DOI: 10.3389/fcvm.2022.938647
|View full text |Cite
|
Sign up to set email alerts
|

Association between remnant cholesterol and heart failure: A prospective cohort study

Abstract: BackgroundElevated remnant cholesterol (RC) is associated with a higher risk of various cardiac diseases. Heart failure (HF) usually occurs at the end stage of various cardiac diseases. However, there is limited research on the association between RC and the risk of HF. Therefore, we aimed to provide relevant evidence by determining whether a high RC level also influences the risk of HF.Materials and methodsIn this secondary analysis of the Atherosclerosis Risk in Communities (ARIC) study, we included 12,595 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The increased risk of HF associated with hypercholesterolemia was also identified in other studies conducted in older adults from Hong Kong [12], the United States [13], and Spain [14]. It is believed that oxidative stress and inflammation triggered by hypercholesterolemia contribute to cardiac remodeling, through processes that include the excessive production of reactive oxygen species, which can cause mitochondrial and cellular damage, consequently favoring HF [40].…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The increased risk of HF associated with hypercholesterolemia was also identified in other studies conducted in older adults from Hong Kong [12], the United States [13], and Spain [14]. It is believed that oxidative stress and inflammation triggered by hypercholesterolemia contribute to cardiac remodeling, through processes that include the excessive production of reactive oxygen species, which can cause mitochondrial and cellular damage, consequently favoring HF [40].…”
Section: Discussionmentioning
confidence: 66%
“…It is believed that oxidative stress and inflammation triggered by hypercholesterolemia contribute to cardiac remodeling, through processes that include the excessive production of reactive oxygen species, which can cause mitochondrial and cellular damage, consequently favoring HF [40]. Another hypothesis may involve the formation of atherosclerotic plaques and the associated inflammatory response in the cardiovascular system, contributing to the development of atherosclerosis and inflammation in arteries, and increasing the risk of plaque rupture and cardiovascular events, including HF [13]. Particularly, we also believe that hypercholesterolemia may contribute to the development of diabetes and hypertension, both recognized as contributing factors to HF progression, as described earlier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] Moreover, recent studies have shown that RC is related to incident HF. 9,10 However, the data on the associations of RC levels with LV structure and function are relatively limited. A previous study found that higher RC was related to myocardial dysfunction in type 2 diabetes populations.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Recent studies have found that elevated RC levels are linked to a higher risk of HF. 9,10 Considering the key role of adverse LV structural and functional alterations in the occurrence of HF, data on the association of RC with LV structure and function remain limited. A previous study reported that RC was related to adverse LV functional changes.…”
mentioning
confidence: 99%